Keanekaragaman dan kelimpahan kumbang cerambycid (Coleoptera: Cerambycidae) di Cagar Alam Pangandaran, Jawa Barat - Septiani Dewi Ariska; Tri Atmowidi; Woro Anggraitoningsih Noerdjito (Jurnal Entomologi Indonesia, 2021)
The community structure of cerambycid beetles in an area is closely related to the heterogeneity of woody plants. Pangandaran Nature Reserve is forest located in the peninsula and has unique fauna and flora communities. The study aims to analyze the diversity and abundance of cerambycid beetles in the Pangandaran Nature Reserve. To attract the cerambycid beetles, we used branches of jackfruit (Artocarpus heterophyllus) and fig (Ficus septica) as traps. Traps were tied in a tree or log about 1.5 m from the ground in the Nature Recreation Park and the Nature Reserve, each area with 2 locations. Collection of beetles were carried out by beating method. A total of 574 individuals cerambycid beetles were found, belonging to 1 subfamily, 8 tribes, 12 genera, and 20 species. The highest species diversity of beetles was found in Nature Recreation Park-1 (H’ = 2.09, E = 0.74), followed by Nature Reserve-2 (H’ = 1.75, E = 0.68), Nature Recreation Park-2 (H’ = 1.70, E = 0.71), and Nature Reserve-1 (H’ = 1.52, E = 0.69). Four species of beetles found in high abundance were Sybra binotata Gahan (229 individuals), Nyctimenius javanus (74 individuals), Atimura bacillina Pascoe (67 individuals), and Acalolepta rusticatrix (Fabricius) (45 individuals). The number of individual beetles collected in Artocarpus (342 individuals) was higher than Ficus traps (232 individuals). This study identified seven endemic beetles of Java, i.e., Myagrus javanicus Breuning, Cacia curta Breuning, Sybra obliquefasciata Breuning, Sybra fuscotriangularis Breuning, Pterolophia triangularis Breuning, N. javanus, and Exocentrus artocarpi Fisher.